Secure Communication Scheme Based on a New 3-D Jerk Chaotic System - A. Rahman, Zain-Aldeen S.; Basil H. Jasim; Ehsan Alhamdawee (Al-Qadisiyah Journal of Pure Science, 2022)
Chaos theory plays a significant role in the engineering fields and especially in the security of data transmission in communication systems. In this paper, a new 3-D jerk chaotic system has been suggested. The fundamental dynamical properties, including the fixed points, chaotic attractors, bifurcation diagrams, and Lyapunov exponents are investigated. In communication systems, data security and the implementation of designed transceivers of secure communication scheme can be considered the main challenge for applying such systems. In this work, a 3-D new jerk chaotic scheme has been proposed to be used in data encryption of communication systems. The proposed jerk chaotic system is used for constructing identical transceivers of communication scheme that are presented by a master (transmitter) and a slave (receiver). In the master end, a useful information beam is encrypted through a chaotic signal. On the other hand, in the slave side, the original information beam is retrieved from the mutual transmitted beam by a chaotic synchronization mechanism. The communication scheme transceivers are synchronized by an adaptive observer synchronization mechanism. Finally, the system is tested and evaluated on a stream of binary information that is encrypted in the transmitter and recovered in the receiver. The results show that our proposal cryptosystem has good performance in term of securing transmitted data.